Improving protein hydrolysis and digestibility in Arthrospira platensis biomass through recombinant peptidases (EC 3.4): Opportunities for monogastric animal diets - Maria P. Spínola; Mónica M. Costa; Rita S. Simões; Vânia O. Fernandes; Vânia Cardoso; Virgínia M.R. Pires; Cláudia Afonso; Carlos Cardoso; Narcisa M. Bandarra; Carlos M.G.A. Fontes; José A.M. Prates (Heliyon)
This study investigates the use of recombinant peptidases (EC 3.4) to improve protein hydrolysis and digestibility in Arthrospira platensis, with a focus on addressing the challenge of reduced protein bioavailability for monogastric animals due to resistant protein-pigment formations, such as phycocyanin, and increased digesta viscosity caused by jellification properties. A library of 192 peptidases was generated, from which 142 soluble peptidases were expressed in Escherichia coli and subsequently screened for activity against an A. platensis suspension in vitro. Among these peptidases, six promising candidates were identified for protein and peptide extraction from the microalga. These enzymes were tested individually, and in a mix (MIX6), and compared to commercial trypsin and pancreatin. Protein content was determined using the Bradford method and potential peptide formation was measured via an o-phthaldialdehyde (OPA) assay. The protein solubility and hydrolysis, specifically of two main protein fractions (18–26 kDa and 40–48 kDa) along with minor fractions, were analysed via 14 % sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Results indicated that the enzyme ID 138, a serine-peptidase, significantly increased total peptide formation in the A. platensis supernatant, although it did not outperform other peptidases or enzyme mixtures. Notably, enzymes ID 152, derived from a marine bacterium, and ID 153, another serine-peptidase, exhibited significant improvements in the extraction and hydrolysis of one protein fraction (18–26 kDa), possibly corresponding to a phycocyanin fraction. While no synergistic effects were observed among peptidases, further investigations are warranted to understand the enzyme composition of MIX6, particularly enzymes ID 138, ID 152 and ID 153, and their potential to enhance the bioavailability of A. platensis proteins for monogastric animals when incorporated into dietary formulations.